PELATIHAN PENERAPAN PROGRAM GIZI KERJA PADA TENAGA KESEHATAN DI RSU SEMBIRING - Elmina Tampubolon; Diana Sinulingga; Ripai Siregar; Tedty Rohaya Tinambunan (INSTITUT KESEHATAN DELI HUSADA, 2021)
As one of the most important health service departments, the daily activities of the hospital must produce good performance. Therefore it must be managed properly, otherwise it will be a source of problems that will impact health workers and the work productivity of employees in hospitals and medical personnel themselves. One of the things that is important to note is the work nutrition of hospital employees. Work nutrition has a positive synergy with employee productivity. If the employee's work nutrition is fulfilled properly, the employee's performance will also be good and increase. Likewise, if the work nutrition is not enough, the productivity will also decrease. By improving the handling of good work nutrition improvement and if the work nutrition program is not implemented properly it will have a negative impact, one of which is a decrease in the work productivity of employees so that it is not optimal in work, thus it is necessary to increase the level of knowledge of human resources in managing work nutrition, and the impact can affect the creation of poor quality performance which is the cause of various health problems, therefore it is necessary to apply laws and regulations to monitor various health factors in accordance with the principles of improving the work nutrition program. This training and counseling proposes a management model for the work nutrition program at the Sembiring hospital to create healthy health workers with good and satisfying performance.